import system_of_complexes.basic universe variables u noncomputable theory open_locale nnreal open category_theory opposite normed_add_group_hom system_of_complexes variables (M M' N : system_of_complexes.{u}) (f : M ⟶ M') (g : M' ⟶ N) /-- The normed snake lemma, weak version. See Proposition 9.10 from Analytic.pdf -/ --TODO Add the non weak version for complete system of complexes lemma weak_normed_snake {k k' k'' K K' K'' : ℝ≥0} [hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] [hk'' : fact (1 ≤ k'')] {m : ℕ} {c₀ : ℝ≥0} (hM : M.is_weak_bounded_exact k K (m+1) c₀) (hM' : M'.is_weak_bounded_exact k' K' (m+1) c₀) (hM'_adm : M'.admissible) (hf : ∀ c i, (f.apply : M c i ⟶ M' c i).norm_noninc) (Hf : ∀ (c : ℝ≥0) [fact (c₀ ≤ c)] (i : ℕ) (hi : i ≤ m+1+1) (x : M (k'' * c) i), ∥(res x : M c i)∥ ≤ K'' * ∥f x∥) (hg : ∀ c i, (g.apply : M' c i ⟶ N c i).ker = f.apply.range) (hgquot : system_of_complexes.is_quotient g) : N.is_weak_bounded_exact (k''*k*k') (K'*(K*K'' + 1)) m c₀ := begin introsI c hc i hi, let c₁ := k'' * (k * (k' * c)), suffices : ∀ n : N c₁ i, ∀ ε > 0, ∃ i₀ (hi₀ : i₀ = i - 1) (y : N c i₀), ∥res n - N.d _ _ y∥ ≤ K' * (K * K'' + 1) * ∥N.d i (i+1) n∥ + ε, { dsimp [c₁] at this, intros n₁ ε hε, haveI hc : fact (k'' * k * k' * c = c₁) := { out := (mul_assoc _ _ _).trans ((mul_assoc _ _ _).trans rfl) }, rcases this (res n₁) ε hε with ⟨i₀, hi₀, y, hy⟩, rw [res_res, d_res] at hy, refine ⟨i₀, _, hi₀, rfl, _⟩, refine ⟨y, hy.trans (add_le_add_right (mul_le_mul_of_nonneg_left _ _) ε)⟩, { apply (admissible_of_quotient hgquot hM'_adm).res_norm_noninc }, { exact (nnreal.zero_le_coe : 0 ≤ K' * (K * K'' + 1)) } }, intros n ε hε, let ε₁ := ε/(K' * (K * K'' + 2) + 1), have hε₁ : 0 < ε₁ := div_pos hε (lt_of_lt_of_le zero_lt_one (nnreal.one_le_add'.out : 1 ≤ K' * (K * K'' + 2) + 1)), obtain ⟨m' : M' c₁ i, rfl : g m' = n⟩ := (hgquot _ _).surjective _, let m₁' := M'.d i (i+1) m', have hm₁' : g m₁' = N.d i (i+1) (g m') := (d_apply _ _ g m').symm, obtain ⟨m₁'' : M' c₁ (i+1), hgm₁'' : g m₁'' = N.d i (i+1) (g m'), hnorm_m₁'' : ∥m₁''∥ < ∥N.d i (i+1) (g m')∥ + ε₁⟩ := (hgquot _ _).norm_lift hε₁ (N.d i (i+1) (g m')), obtain ⟨m₁, hm₁⟩ : ∃ m₁ : M c₁ (i+1), f m₁ + m₁'' = m₁', { have hrange : m₁' - m₁'' ∈ f.apply.range, { rw [← hg _ _, mem_ker _ _, _root_.map_sub], change g m₁' - g m₁'' = 0, rw [hm₁', hgm₁'', sub_self] }, obtain ⟨m₁, hm₁ : f m₁ = m₁' - m₁''⟩ := (mem_range _ _).1 hrange, exact ⟨m₁, by rw [hm₁, sub_add_cancel]⟩ }, have him : i+2 ≤ m+2 := add_le_add_right hi _, have hm₂ : f (M.d (i+1) (i+2) m₁) = -M'.d (i+1) (i+2) m₁'', { rw [← d_apply, eq_sub_of_add_eq hm₁, _root_.map_sub, ← category_theory.comp_apply, d_comp_d, coe_zero, ← neg_inj, pi.zero_apply, zero_sub], }, have hle : ∥res (M.d (i+1) (i+2) m₁)∥ ≤ K'' * ∥m₁''∥, { calc ∥res (M.d (i+1) (i+2) m₁)∥ ≤ K'' * ∥f (M.d (i+1) (i+2) m₁)∥ : Hf _ _ him _ ... = K'' * ∥M'.d (i+1) (i+2) m₁''∥ : by rw [hm₂, norm_neg] ... ≤ K'' * ∥m₁''∥ : (mul_le_mul_of_nonneg_left (hM'_adm.d_norm_noninc _ _ _ _ m₁'') $ nnreal.coe_nonneg K'') }, obtain ⟨i', j, hi', rfl, m₀, hm₀⟩ := hM _ ⟨hc.out.trans $ le_mul_of_one_le_left' hk'.out⟩ _ (nat.succ_le_succ hi) (res m₁) ε₁ hε₁, rw [← nat.pred_eq_sub_one, i.pred_succ] at hi', subst i', replace hm₀ : ∥res m₁ - M.d i (i+1) m₀∥ ≤ K * K'' * ∥N.d i (i+1) (g m')∥ + K*K''*ε₁ + ε₁, { calc ∥res m₁ - M.d i (i+1) m₀∥ = ∥res (res m₁) - M.d i (i+1) m₀∥ : by rw res_res ... ≤ K * ∥M.d (i+1) (i+2) (res m₁)∥ + ε₁ : hm₀ ... = K * ∥res (M.d (i+1) (i+2) m₁)∥ + ε₁ : by rw d_res ... ≤ K*(K'' * ∥m₁''∥) + ε₁ : add_le_add_right (mul_le_mul_of_nonneg_left hle nnreal.zero_le_coe) _ ... ≤ K*(K'' * (∥N.d i (i+1) (g m')∥ + ε₁)) + ε₁ : add_le_add_right (mul_le_mul_of_nonneg_left (mul_le_mul_of_nonneg_left hnorm_m₁''.le nnreal.zero_le_coe) nnreal.zero_le_coe) ε₁ ... = K * K'' * ∥N.d i (i+1) (g m')∥ + K*K''*ε₁ + ε₁ : by ring }, let mnew₁' := M'.d i (i+1) (res m' - f m₀), have hmnew' : mnew₁' = res m₁'' + f (res m₁ - M.d i (i+1) m₀), { calc mnew₁' = M'.d i (i+1) (res m' - f m₀) : rfl ... = res (M'.d i (i+1) m') - (f (M.d i (i+1) m₀)) : by rw [_root_.map_sub, d_res _, d_apply] ... = res (M'.d i (i+1) m') - (f (res m₁)) + (f (res m₁) - f (M.d i (i+1) m₀)) : by abel ... = res m₁'' + f ((res m₁) - (M.d i (i+1) m₀)) : by { rw [← system_of_complexes.map_sub, ← res_apply, ← _root_.map_sub, ← sub_eq_of_eq_add' hm₁.symm] } }, have hnormle : ∥mnew₁'∥ ≤ (K*K'' + 1)*∥N.d i (i+1) (g m')∥ + (K*K'' + 2) * ε₁, { calc ∥mnew₁'∥ = ∥res m₁'' + f (res m₁ - M.d i (i+1) m₀)∥ : by rw [hmnew'] ... ≤ ∥res m₁''∥ + ∥f (res m₁ - M.d i (i+1) m₀)∥ : norm_add_le _ _ ... ≤ ∥m₁''∥ + ∥f (res m₁ - M.d i (i+1) m₀)∥ : add_le_add_right (hM'_adm.res_norm_noninc _ _ _ _ m₁'') _ ... ≤ ∥m₁''∥ + ∥res m₁ - M.d i (i+1) m₀∥ : add_le_add_left (hf _ _ _) _ ... ≤ ∥N.d i (i+1) (g m')∥ + ε₁ + ∥res m₁ - M.d i (i+1) m₀∥ : add_le_add_right (le_of_lt hnorm_m₁'') _ ... ≤ ∥N.d i (i+1) (g m')∥ + ε₁ + (K * K'' * ∥N.d i (i+1) (g m')∥ + K * K'' * ε₁ + ε₁) : add_le_add_left hm₀ _ ... = (K*K'' + 1)*∥d _ _ (i+1) (g m')∥ + (K*K'' + 2) * ε₁ : by ring }, obtain ⟨i₀, _, hi₀, rfl, mnew₀, hmnew₀⟩ := hM' _ hc _ (hi.trans m.le_succ) (res m' - f m₀) _ hε₁, replace hmnew₀ : ∥res (res m' - f m₀) - d _ _ _ mnew₀∥ ≤ K' * ((K * K'' + 1) * ∥N.d i (i+1) (g m')∥ + (K * K'' + 2) * ε₁) + ε₁ := hmnew₀.trans (add_le_add_right (mul_le_mul_of_nonneg_left hnormle nnreal.zero_le_coe) ε₁), let nnew₀ : ↥(N c i₀) := g mnew₀, have hmnewlift : g (res (res m' - f m₀) - M'.d i₀ i mnew₀) = res (g m') - N.d i₀ i nnew₀, { suffices h : g (res m' - f m₀) = res (g m'), { rw [system_of_complexes.map_sub, ← res_apply, ← d_apply, h, res_res] }, rw system_of_complexes.map_sub, have hker : f m₀ ∈ g.apply.ker, { rw [hg _ _, mem_range _ _], exact ⟨m₀, rfl⟩ }, replace hker : g (f m₀) = 0, { rwa mem_ker at hker }, rw [hker, sub_zero, ← res_apply] }, refine ⟨i₀, hi₀, nnew₀, _⟩, rw ← hmnewlift, refine ((hgquot _ _).norm_le _).trans (hmnew₀.trans (le_of_eq _)), have hε₁_ε : (K' * (K * K'' + 2) + 1 : ℝ)*ε₁ = ε := mul_div_cancel' _ (by { refine (lt_of_lt_of_le zero_lt_one _).ne', exact (nnreal.one_le_add'.out : 1 ≤ K' * (K * K'' + 2) + 1) }), rw ← hε₁_ε, ring, end